Intracellular and Extracellular Biomineralization Induced by Klebsiella pneumoniae LH1 Isolated from Dolomites. Issue 3 (15th March 2020) - Zhao, Yanyang; Han, Zuozhen; Yan, Huaxiao; Zhao, Hui; Tucker, Maurice E.; Han, Mei; Mao, Guangzhou; Yin, Junxiao
Abstract: The interaction between bacteria and minerals is very complicated and has been intensively studied in the laboratory and the field in the last few decades, but the processes and mechanisms of biomineralization and mineral precipitation are still not fully understood and need to be explored further. In the present work, biomineralization experiments were undertaken using Klebsiella pneumoniae LH1, collected from a natural surface environment in an area of outcrops of Cambrian dolomite, in a culture medium with various Mg/Ca molar ratios (0, 3, 6 and 12). The mineral precipitates obtained were analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive spectrometer (EDS), Fourier transform infrared spectrometer (FTIR), laser scanning confocal microscopy (LSCM) and X-ray photoelectron spectroscopy (XPS). Cells were analyzed with a scanning transmission electron microscope (STEM), high resolution transmission electron microscope (HRTEM) and selected area electron diffraction (SAED). The composition of amino acids in extracellular polymeric substances (EPS) was also determined. In the experiments it was found that the production of ammonia and the presence of carbonate anhydrase promoted the increase of the medium pH and that minerals are nucleated on the EPS, which consist chiefly of amino acids and negatively-charged organic functional groups. With increasing Mg/Ca ratios, the mineral phases changed, including calcite (100%) at Mg/Ca molar ratio of 0, monohydrocalcite (36.05%) + dypingite (63.95%) at Mg/Ca molar ratio of 3, monohydrocalcite (29.72%) + dypingite (15.48%) + nesquehonite (54.80%) at Mg/Ca molar ratio of 6, and monohydrocalcite (14.2%) + dypingite (1.0%) + nesquehonite (84.80%) at Mg/Ca molar ratio of 12. Some intracellular amorphous calcium- and magnesium-rich inclusions were also detected in K. pneumoniae LH1, suggesting intracellular biomineralization accompanying the extracellular mineral precipitation. This study provides further understanding of the biomineralization processes of microorganisms.